Effect of Lactobacillus plantarum PS128 on neuromuscular efficiency after a half-marathon - Yu, Chia-Hsien; Lai, Chang-Chi; Chen, Jing-Hsuan; Chen, I-Cheng; Tai, Hsia-Ling; Fu, Szu-Kai (Frontiers in Physiology, 2023)
The use of Lactobacillus plantarum PS128 (PS128) could be considered an antioxantioxidant supplementidation to reduce muscle fatigue and improve exercise capacity recovery after vigorous exercise.The purpose is to investigate the effect of PS128 on muscle fatigue and electromyography (EMG) activity after half-marathon (HM).The experimental design used the repeated-measured design with double blind. The participants took PS128 for 4 weeks as the PS128 group (PSG, n = 8), or took 2 capsules of placebo for 4 weeks as the placebo group (PLG, n = 8) to make counter balanced. The time points of maximal voluntary isometric contraction (MVIC) and EMG activity test were set before probiotics taking (baseline), 48 hours before HM (Pre) and immediately (0h), 3 hours (3h), 24 hours (24h), 48 hours (48h), 72 hours (72h), and 96 hours (96h) after HM.Results: EMG activity included median power frequency (MDF), integrated EMG (iEMG), and neuromuscular efficiency (NME) (peak torque / iEMG). MVICs of knee extensors analyzed by isokinetic dynamometer was showed decreasing from the Pre to 0h (p = 0.0001), 3h (p < 0.0001), 24h (p < 0.0001), 48h (p < 0.0001), 72h (p = 0.0002), and 96h (p = 0.0408) time point in PLG. Sidak's multiple comparisons tests showed that the PLG was significantly lower than PSG at 0h (p = 0.0173), 3h (p < 0.0001), 24h (p < 0.0001), 48h (p < 0.0001), 72h (p < 0.0001), and 96h (p = 0.0004) time point. The MDF of vastus medialis oblique (VMO) in PLG was significantly decreased 24 hours after HM, and significantly lower than in PSG at all the times points after HM. The iEMG of VMO in PLG was significantly decreased 48 hours after HM, and significantly lower than in PSG at 0 h post, 3 h post, 24 h post, 48 h post, and 72 h post after HM.The PS128 supplementation may prevent the decrease in MDF, iEMG, and peak torque after vigorous exercise. Recreational runners may consider implementing a probiotic supplementation regimen as a potential strategy to mitigate muscle fatigue following a HM.